The many deaths of Peter and Paul - Eastman, David L. (Oxford early Christian studies, 2019)
This study examines major narrative elements of the martyrdom accounts of Peter and Paul and explores the variety concerning whether the apostles died separately or together, why they died, when they died, where they died, and what happened to their bodies after their deaths.